we have
-------> inequality 1
or
-------> inequality 2
we know that
In this system of inequalities, for a value to be the solution of the system, it is enough that it satisfies at least one of the two inequalities.
let's check each of the values
<u>case 1)</u> x=-6
<u>Substitute the value of x=-6 in the inequality 1</u>
![4(-6 + 3) \leq 0](https://tex.z-dn.net/?f=4%28-6%20%2B%203%29%20%5Cleq%200)
![4(-3) \leq 0](https://tex.z-dn.net/?f=4%28-3%29%20%5Cleq%200)
-------> is ok
The value of x=-6 is a solution of the compound inequality-----> It is not necessary to check the second inequality, because the first one satisfies
<u>case 2)</u> x=-3
<u>Substitute the value of x=-3 in the inequality 1</u>
![4(-3 + 3) \leq 0](https://tex.z-dn.net/?f=4%28-3%20%2B%203%29%20%5Cleq%200)
![4(0) \leq 0](https://tex.z-dn.net/?f=4%280%29%20%5Cleq%200)
-------> is ok
The value of x=-3 is a solution of the compound inequality-----> It is not necessary to check the second inequality, because the first one satisfies
<u>case 3)</u> x=0
<u>Substitute the value of x=0 in the inequality 1</u>
![4(0 + 3) \leq 0](https://tex.z-dn.net/?f=4%280%20%2B%203%29%20%5Cleq%200)
![4(3) \leq 0](https://tex.z-dn.net/?f=4%283%29%20%5Cleq%200)
-------> is not ok
<u>Substitute the value of x=0 in the inequality 2</u>
![0 + 1 > 3](https://tex.z-dn.net/?f=0%20%2B%201%20%3E%203)
--------> is not ok
The value of x=0 is not a solution of the compound inequality
case 4) x=3
<u>Substitute the value of x=3 in the inequality 1</u>
![4(3 + 3) \leq 0](https://tex.z-dn.net/?f=4%283%20%2B%203%29%20%5Cleq%200)
![4(6) \leq 0](https://tex.z-dn.net/?f=4%286%29%20%5Cleq%200)
-------> is not ok
<u>Substitute the value of x=3 in the inequality 2</u>
![3 + 1 > 3](https://tex.z-dn.net/?f=3%20%2B%201%20%3E%203)
--------> is ok
The value of x=3 is a solution of the compound inequality
case 5) x=8
<u>Substitute the value of x=8 in the inequality 1</u>
![4(8 + 3) \leq 0](https://tex.z-dn.net/?f=4%288%20%2B%203%29%20%5Cleq%200)
![4(11) \leq 0](https://tex.z-dn.net/?f=4%2811%29%20%5Cleq%200)
-------> is not ok
<u>Substitute the value of x=8 in the inequality 2</u>
![8 + 1 > 3](https://tex.z-dn.net/?f=8%20%2B%201%20%3E%203)
--------> is ok
The value of x=8 is a solution of the compound inequality
<u>case 6)</u> x=10
<u>Substitute the value of x=10 in the inequality 1</u>
![4(10 + 3) \leq 0](https://tex.z-dn.net/?f=4%2810%20%2B%203%29%20%5Cleq%200)
![4(13) \leq 0](https://tex.z-dn.net/?f=4%2813%29%20%5Cleq%200)
-------> is not ok
<u>Substitute the value of x=10 in the inequality 2</u>
![10+ 1 > 3](https://tex.z-dn.net/?f=10%2B%201%20%3E%203)
--------> is ok
The value of x=10 is a solution of the compound inequality
therefore
<u>the answer is</u>
[-6,-3,3,8,10]